2017
DOI: 10.1155/2017/7236970
|View full text |Cite
|
Sign up to set email alerts
|

Standard versus Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Prospective Randomized Study

Abstract: Symptomatic spondylolisthesis patients may benefit from surgical decompression and stabilization. The standard (S) technique is a transforaminal lumbar interbody fusion (TLIF). Newer, minimally invasive (MI) techniques seem to provide similar results with less morbidity. We enrolled patients with at least 6 months of symptoms and image-confirmed low-grade spondylolisthesis, at a single academic institution, between 2011 and 2015. The patients were randomized to either S or MI TLIF. The primary outcome measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 10 publications
0
65
0
Order By: Relevance
“…Wang et al [ 16 ] demonstrated that minimally invasive TLIF has similar surgical efficacy with the traditional open TLIF in treating one-level degenerative lumbar diseases. Serban et al [ 15 ] justified the two techniques provided similar clinical and radiological outcomes. Seng et al [ 14 ] showed MI-TLIF is comparable with open TLIF in terms of midterm clinical outcomes and fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 16 ] demonstrated that minimally invasive TLIF has similar surgical efficacy with the traditional open TLIF in treating one-level degenerative lumbar diseases. Serban et al [ 15 ] justified the two techniques provided similar clinical and radiological outcomes. Seng et al [ 14 ] showed MI-TLIF is comparable with open TLIF in terms of midterm clinical outcomes and fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…There were 17 articles showing results of those parameters. [1][2][3][4][5][6][7][8][9][10][11][12][15][16][17][18][19] Results during the perioperative period were reviewed. Operative time was variable.…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…1,3,16,35 Although MIS TLIF is associated with a significant learning curve, increased use of fluoroscopy, and risk of nerve injury, 2,6,[26][27][28][44][45][46][47] its benefits over open TLIF include decreased operating time, decreased intraoperative blood loss, decreased hospital stay, improved cost-effectiveness, faster return to work, and decreased pain. 20,24,29,32,[37][38][39]42 One controversy with MIS TLIF is the ability to provide adequate reduction of spondylolisthesis and correction of radiographic parameters, or even whether such changes are necessary. 7,8,14,30,33,40 With a growing body of evidence emphasizing the finding that the restoration and maintenance of spinopelvic parameters after spine surgery is associated with improved outcomes, 5,12,17,18,25,34,36,41 there has been interest in applying these principles to MIS TLIF as well.…”
mentioning
confidence: 99%